Addressing the student: Voice elements in educational texts - Sangers, Nina; Evers-Vermeul, Jacqueline; Hoeken, Hans (Dutch Journal of Applied Linguistics, 2022)
Voice elements are those elements of educational texts that authors use to interact with students, such as questions, evaluations, or direct address forms (“you”). These elements are intended to enhance students’ engagement and comprehension, but we know little about the extent to which they are used in present-day educational texts. Using a corpus of Dutch biology, geography, and history texts for grade 5 and grade 8 (N=1055), this study shows that voice elements are barely differentiated over grade levels. Conversely, voice elements are generally diversified over school subjects, as they are less frequent in history texts, which convey readily imaginable and relatable content, compared to biology and geography texts, which discuss less relatable content for which students need to exert more effort to connect it to their own world. This finding suggests that authors of educational texts have intuitions about the conditions under which voice elements are a desirable attribute.